Assessment of Carbon Footprint in Different Industrial Sectors, Volume 1 - Muthu, Subramanian Senthilkannan; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2014)
Carbon footprint is one of the important environmental impacts, which has received greater attention from the public, government and media. It is one of the important topics of even any government$1 (Bs agenda as well and every nation is trying its best to reduce its carbon footprint to the maximum possible extent. Every company would like to reduce the carbon footprint of its products and consumers are looking for the products which emit lower carbon emissions in their entire life cycle. Assessment of Carbon footprint for different products, processes and services and also carbon labelling of products have become familiar topics in the recent past in various industrial sectors. Every industry has its unique assessment and modelling techniques, allocation procedures, mitigation methods and labelling strategies for its carbon emissions. With this background, this book has been framed with dedicated chapters on carbon footprint assessment on various industrial sectors. In each chapter, details pertaining to the assessment methodologies of carbon footprint followed in a particular industry, challenges in calculating the carbon footprint, case studies of various products in that particular industry, mitigation measures to be followed to trim down the carbon footprint, recommendations for further research are discussed in detail. This first volume includes the carbon footprint assessment methodology of agricultural sector, telecommunication sector, food sector, ceramic industry, packaging industry, building and construction sector and solid waste sector.s
Introduction to the eco-design methodology and the role of Product Carbon Footprint -- Carbon footprint estimation of agriculture sector -- Methodology for Determining the Carbon Footprint of the Construction Of Residential Buildings -- Carbon Footprint of Food Products -- The carbon footprint of ceramic products -- Carbon footprint of mobile devices: Open questions in carbon footprinting of emerging mobile ICT technologies -- The carbon footprint of pigmeat in Flanders -- Carbon emission and carbon footprint of different industrial spaces in different regions of China -- Ecodesign and Product Carbon Footprint use in the packaging sector -- Carbon Footprint of Crop Production and the Significance for GHGs Reduction in Agriculture Sector of China -- Carbon footprint of solid waste sector in Greater Bangalore, India.
Keywords: Environmental sciences; Industrial engineering; Environmental management; Biotechnology; Sustainable development; Environment; Environmental Management; Production/Logistics/Supply Chain Management; Industrial and Production Engineering; Environmental Engineering/Biotechnology.; Sustainable Development